KEEFEKTIFAN TEKNIK MIND MAP DALAM PEMBELAJARAN MENULIS KARANGAN DESKRIPSI (Studi Eksperimen pada Siswa Kelas IV SDIT Atikah Musaddad Garut Tahun Pelajaran 2013 - 2014) - Eneng Sri Mulyaty (Jurnal PGSD UNIGA, 2023)
This essay titled “The Effectiveness Of Mind Mapping Technique In Teaching Essay Writing Descriptions (Experimental Studies in  Grade IV SDIT Atikah Musaddad In 2013-2014 School Year) Mind map technique is the one of writing technique with brain comprehensive approach in order to make comprehensive note in one page. Mind map use visual image and the other graphical instrument to give deeper impression. Mind map technique imitate the workings of the brain record and remember the information through symbol, picture, emotional meaning, and color. Mind map technique make the information or cognition easier to be memorized and pleasure. In  learning to write description essay, teachers often use learning techniques that are less fun for their student. Moreover, the student are faced with the problem difficulty in pouring the resulting picture of sensing the object. Because of this, researchers try to apply mind mapping technique in teaching writing descriptive essays to determine the effectiveness of these techniques.Researches propose the following research problems with 1) how the mind map preparation techniques in teaching essay writing descriptions in grade IV SDIT Atikah Musaddad in 2013-2014 school year ?. 2) how the implementation of mind mapping technique in teaching essay writing descriptions in grade IV SDIT Atikah Musaddad in 2013-2014 school year ?. 3) how the effectiveness of mind mapping technique in teaching essay writing descriptions grade IV SDIT Atikah Musaddad in 2013-2014 school year?This research uses experimental methods with  one-group pretest posttest design.  Samples used in this study were students in grade IV SDIT Atikah Musaddad in 2013-2014 school year. Procedures conducted research as much as 2 meetings. Pretest and posttest values taken from every encounter with the object descriptions of different themes. Based on the hypothesis testing results show that the mind mapping technique effectively used in teaching essay writing descriptions. The results obtained from the two sample paired t test, t count =2,50 > from t table = 2,06  at the first meeting and t count =3,76  > from t table = 2,06 at the second meeting.  Besides that, the data gain suggest that increased students' ability to write essays every meeting including low category with a value of 0.1. Thus conclude that learning to write essays descriptions mind mapping technique in grade IV SDIT Atikah Musaddad in 2013-2014 school year effectively used despite the increase include the category of low. The study is expected to be the basis for other research done on mind map technique with the indicator as well as different objects.